2023
DOI: 10.1002/pmic.202200542
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proteoforms by top‐down proteomics using two‐dimensional low/low pH reversed‐phase liquid chromatography‐mass spectrometry

Abstract: In top‐down (TD) proteomics, efficient proteoform separation is crucial to reduce the sample complexity and increase the depth of the analysis. Here, we developed a two‐dimensional low pH/low pH reversed‐phase liquid chromatography separation scheme for TD proteomics. The first dimension for offline fractionation was performed using a polymeric reversed‐phase (PLRP‐S) column with trifluoroacetic acid as ion‐pairing reagent. The second dimension, a C4 nanocolumn with formic acid as ion‐pairing reagent, was coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Spectral simplification can counterbalance these effects. Recent studies have demonstrated that the use of field asymmetric ion mobility spectrometry (FAIMS) can lead to deeper characterization of intact proteomes in the 0–30 kDa mass range. Three recent studies by Tholey and co-workers have first described the benefits of internal stepping of the compensatory DC voltages (compensation voltage, C.V.) applied to the central electrode of the FAIMS apparatus during a single LC–FAIMS–MS 2 analysis of proteoforms from CaCo-2 cells, , and then proven the compatibility of such data acquisition method with off-line protein fractionation via passively eluting proteins from polyacrylamide gels as intact species (PEPPI) . In the latter study, FAIMS-enabled gas-phase fractionation of intact protein ions led to the identification of more than 8500 low-molecular weight (MW) proteoforms.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral simplification can counterbalance these effects. Recent studies have demonstrated that the use of field asymmetric ion mobility spectrometry (FAIMS) can lead to deeper characterization of intact proteomes in the 0–30 kDa mass range. Three recent studies by Tholey and co-workers have first described the benefits of internal stepping of the compensatory DC voltages (compensation voltage, C.V.) applied to the central electrode of the FAIMS apparatus during a single LC–FAIMS–MS 2 analysis of proteoforms from CaCo-2 cells, , and then proven the compatibility of such data acquisition method with off-line protein fractionation via passively eluting proteins from polyacrylamide gels as intact species (PEPPI) . In the latter study, FAIMS-enabled gas-phase fractionation of intact protein ions led to the identification of more than 8500 low-molecular weight (MW) proteoforms.…”
Section: Introductionmentioning
confidence: 99%
“…57 As shown in for MD separation and TDP. 59 In summary, good orthogonality, improved separation efficiency, and more comprehensive protein characterisation has been achieved using high-pH/low-pH RPLC platforms compared with 1D RPLC for TDP.…”
Section: Reversed-phase Liquid Chromatography -Based Multidimensional...mentioning
confidence: 99%
“…This group utilised low‐pH RPLC in both dimensions and employed different ion pairing reagents and stationary phases to change selectivity between the two RPLC dimensions. In addition to concatenation to improve sample throughput, this group demonstrated the first implementation of low‐pH/low‐pH RPLC for MD separation and TDP 59 …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the use of field asymmetric ion mobility spectrometry (FAIMS) 22 can lead to a deeper characterization of intact proteomes in the 0-30 kDa mass range. [23][24][25] Three recent studies by Tholey and co-workers have first described the benefits of internal stepping of the compensatory DC voltages (compensation voltage, C.V.) applied to the central electrode of the FAIMS apparatus during a single LC-FAIMS-MS 2 analysis of proteoforms from CaCo-2 cells, 26,27 and then proven the compatibility of such data acquisition method with off-line protein fractionation 28 via passively eluting proteins from polyacrylamide gels as intact species (PEPPI). 29 In the latter study, FAIMS-enabled gas-phase fractionation of intact protein ions led to the identification of more than 8,500 low-molecular weight (MW) proteoforms.…”
Section: Main Textmentioning
confidence: 99%